Research on Behaviour of Indigenous Farm Animals as a Sine Qua Non for Improving their Productivity and Welfare (Indian Journal of Animal Production and Management, 2024)
Animal behaviour comprises all the ways and  manners in which animals relate with members of  their species, animals of other species and their  environment. India has a large population of  livestock and umpteen breeds inhabiting in diverse  agro-ecological regions. The behavioural repertoire  of these breeds and distinguishing features of  behaviour among different breeds has sparsely  been explored. Knowledge of animal behaviour is a  pivotal area of animal production and welfare, yet  most neglected by researchers, developmental  departments and farmers in India either due to  ignorance or neglect. Behaviour is generally the  animal's “first line of defence” in response to  environmental change. Careful observations of  behaviour can provide with a great deal of  information about animals' requirements,  preferences and dislikes and internal states. An in depth knowledge of behaviours of farm animals,  therefore, is indispensable to their handling,  productivity, welfare and profitability. This paper  attempts to address the importance of studying the  behaviour especially of indigenous breeds of  livestock, which is sine qua non to their handling  and management.
Keywords: behaviour; research; native livestock; production; welfare